ANALISIS PRAKTIK MAHAR SEDERHANA DAN IMPLIKASINYA TERHADAP ISTRI PERSPEKTIF MAQASHID AL-SYARIAH: STUDI KASUS DI KECAMATAN MUMBULSARI, JEMBER - Umeir hudzaifah; Anas Burhanuddin (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research analyzes the practice of simple mahr in marriages within the Mumbulsari district, Jember Regency, and its implications for wives from a maqashid al-syariah perspective. Employing a qualitative approach with field studies, data was collected through in-depth interviews with the head of the Office of Religious Affairs (KUA) and married couples. Research findings indicate that simple mahrs, such as prayer tools and the Quran, dominate practices in Mumbulsari. This practice, when mutually agreed upon, actualizes the values of hifz al-din, hifz al-nafs, and hifz al-maal. The simplicity of mahr not only strengthens marital bonds spiritually and emotionally but also streamlines the marriage process, preventing burdensome practices. These findings suggest that the giving of simple mahr, based on sincerity and mutual agreement, aligns with the fundamental principles of maqashid al-syariah as articulated by al-Syatibi.